DEVELOPMENT OF A MORAL LOVING-BASED CO-CURRICULAR MODULE TO FOSTER CHARACTER AMONG STUDENTS AT PUBLIC ELEMENTARY SCHOOLS IN SOUTH BULANGO DISTRICT, BONE BOLANGO REGENCY - Juniarti Detuage; Zulaecha Ngiu; Candra Cuga (SOSIOEDUKASI, 2026)
This study aims to develop a moral loving-based co-curricular module to strengthen character education for elementary school students. The method used is Research and Development (R&D) employing the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted at two elementary schools in Bulango Selatan Subdistrict, Gorontalo, with fifth-grade students as the subjects. A mixed-methods approach was employed, combining qualitative data from observations and interviews with quantitative data from validation results, practicality tests, and effectiveness tests using a pretest-posttest design. The results of the study indicate that students’ initial character traits were still low, particularly in the aspects of empathy and self-control. The developed module underwent a validation process by experts in curriculum, content, language, and end-users, receiving ratings of “highly suitable” and “practical.” The implementation of the module demonstrated a significant improvement in student character, both quantitatively and qualitatively, marked by increased self-confidence, empathy, honesty, and the ability to control emotions. This study concludes that character education will be more effective if designed as a systematic, experience-based process that integrates action and reflection. Moral loving-based co-curricular modules can serve as an implementational tool that bridges the gap between character education policies and learning practices in schools, and have the potential to support the continuous strengthening of student character through co-curricular activities